2003
DOI: 10.3836/tjm/1244208599
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Knotted Spatial Graphs are Totally Knotted

Abstract: Applying Jaco's Handle Addition Lemma, we give a condition for a 3-manifold to have an incompressible boundary. As an application, we show that the boundary of the exterior of a minimally knotted planar graph is incompressible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Then the innermost disk D in S bounded by an innermost loop of F ∩S is a compressing disk for F since S is an essential tangle decomposing sphere. It follows that r(F, Γ) ≤ |∂D ∩ Γ| ≤ |Γ ∩ S| < n. Figure 5 shows a pair (F, Γ) of a genus two Heegaard surface F and a minimally knotted (hence totally knotted by [15]) handcuff graph Γ which is in a Morse bridge position. To show r(F, Γ) ≥ 2, let D i 1 and D i 2 be meridian disks in a handlebody V i as in Figure 5 and then, following Lemma 2.3, we have a 4-punctured sphere F i 1 .…”
Section: Proofs Of Theoremsmentioning
confidence: 99%
“…Then the innermost disk D in S bounded by an innermost loop of F ∩S is a compressing disk for F since S is an essential tangle decomposing sphere. It follows that r(F, Γ) ≤ |∂D ∩ Γ| ≤ |Γ ∩ S| < n. Figure 5 shows a pair (F, Γ) of a genus two Heegaard surface F and a minimally knotted (hence totally knotted by [15]) handcuff graph Γ which is in a Morse bridge position. To show r(F, Γ) ≥ 2, let D i 1 and D i 2 be meridian disks in a handlebody V i as in Figure 5 and then, following Lemma 2.3, we have a 4-punctured sphere F i 1 .…”
Section: Proofs Of Theoremsmentioning
confidence: 99%
“…On the other hand, it turns out that a genus 2 graph with a bridge sphere having four or fewer punctures, or a vp-bridge torus with two or fewer punctures cannot be Brunnian. We'll use the following theorem of Ozawa and Tsutsumi [24], though not in full generality. The version for genus 2 graphs is not difficult to prove directly.…”
Section: 2mentioning
confidence: 99%
“…A spatial embedding of a planar graph G is said to be minimally knotted if it is non-trivial but f | H is trivial for any proper subgraph H of G. A spatial embedding f : G → S 3 is said to be totally knotted if the natural homomorphism i * : π 1 (∂E(f (G))) → π 1 (E(f (G))) is injective, where E(f (G)) denotes the spatial graph-exterior. The second and the last authors showed the following in [1]. Proof.…”
mentioning
confidence: 90%
“…18. In the eye graph there exist exactly three pairs (γ (1,4,5), γ(6, 9, 12)), (γ (2,3,4), γ(7, 9, 11)), (γ(1, 2, 6, 7), γ(8, 10)) of disjoint cycles, where γ denotes the cycle uniquely determined by the specified labels of edges. It is easy to check that each of the six cycles appeared in these pairs forms a trivial knot, and each corresponding 2-component link is split.…”
Section: Remarksmentioning
confidence: 99%